An Analysis of Jargon Written on the Correspondence by Villas’ Staff in Gianyar, Bali - Luh Nyoman Tri Lilasari (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
Jargon, as part of a sociolinguistic study, is a language variation consists of technical terms or phrases used by a particular profession or group of individuals. The research focuses on the three points of discussion, i.e. forms, meanings, and functions of jargon found in business correspondence written in email by the staffs of Front Office Department and Sales & Marketing Department in Djanuraga villa and Letung villa in Gianyar. Forms of jargon consist of acronym, abbreviation, word, and phrase. The data was collected by observation methods of the business correspondence sent through email and also interview techniques to the employees of the Front Office department and Sales & Marketing department in the villas. Qualitative descriptive method was used to analyze data in this study. The finding in the forms of jargon that acronym is the most frequent one used in the correspondence, with 23 data and the second is abbreviation with 6 data. Regarding to the meaning of the jargon, the jargon is described clearly to make the staffs understand about the jargon more clearly. According to the finding of the functions of jargon in the correspondence used by villas’ staffs, the data analysis reveals that there are two functions, i.e. providing a technical or specialist language for particular purpose and as a sign of professionalism that showing sufficient work experience and to make communication more effective.